Modeling pore-scale calcite dissolution kinetics - Sánchez Guiscardo, Guillermo; Idiart, Andrés; Abarca, Elena; Paz-García, Juan Manuel (My University, 2022)
The study of the kinetics of heterogeneous solid-fluid reactions, such as dissolution- precipitation reactions is difficult due to the characterization of the solid-fluid interphase properties, and the possibility for the reaction rate to be limited by different phenomena, such as pore diffusion, surface kinetics, or electric double layer repulsion. Herein, a model for the porous scale dissolution of a calcite particle summited to an incident flow containing certain level of acidity is presented. First, the Chemical Reaction Engineering physics has been used to model the set of chemical reactions defining the chemical problem, including the surface of the calcite particle, CaCO3(s), and the aqueous species Ca2+, CO2-, HCO-, H2CO3, H+ and OH-. Then, a “space-dependent model” has been created to include coupling with the Transport of Dilute Species and Laminar Flow physics. Additionally, the physics “Secondary Current Distribution” has also been used in this model to use the functionalities of the “Deforming Electrode Surface”, and modeling the surface of the calcite particle as a non-faradic reaction. This way, the changes of volume of the solid particle, due to the dissolution process, has been incorporated. The model is kinetically controlled by the surface reaction rate, and the diffusion – convection rates. Aqueous species are modelled as instantaneous reversible (equilibrium) reactions. The fully-coupled reactive transport model is able to predict the dissolution of the calcite particle and the corresponding size change. Furthermore, if strong concentration gradients are created between the front and the back of the particle, the dissolution results in a deformation of the circular geometry.
Keywords: Soporte lógico; Aplicaciones informáticas; Ingeniería química; Calcita; COMSOL; PHREEQC; Calcite